Pharmacokinetics of imidocarb dipropionate in white‐tailed deer (Odocoileus virginianus) after single intramuscular administration. Issue 1 (1st April 2019) - Milnes, Ellie L.; Delnatte, Pauline; Woodbury, Murray; Hering, Adam; Lee, Sam; Smith, Dale A.; Nemeth, Nicole M.; Gu, Yu; Gehring, Ronette; Johnson, Ron
Abstract: This study was designed to investigate the pharmacokinetics of imidocarb, a carbanilide derivative, in white‐tailed deer ( Odocoileus virginianus ). The pharmacokinetic properties of a single intramuscular (IM) dose of imidocarb were determined in 10 deer. A single IM injection of 3.0 mg/kg imidocarb dipropionate was administered, and blood samples were collected prior to, and up to 48 hr after imidocarb administration. Plasma imidocarb concentrations were determined by high‐performance liquid chromatography with ultraviolet detection. The disposition of plasma imidocarb was best characterized by a two‐compartment open model. The mean ± SE maximal imidocarb concentration in deer was 880.78 ± 81.12 ng/ml at 38.63 ± 5.30 min postinjection. The distribution phase had a half‐life ( t 1/2 α ) of 25.90 ± 10.21 min, and plasma imidocarb concentration declined with a terminal elimination half‐life ( t 1/2 β ) of 464.06 ± 104.08 min (7.73 ± 1.73 hr). Apparent volume of distribution based on the terminal phase ( V Z / F ) was 9.20 ± 2.70 L/kg, and apparent total body clearance (Cl/ F ) was 15.97 ± 1.28 ml min −1 kg −1 .